2022
DOI: 10.1186/s12913-021-07428-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of switching from partially combined vaccine “Pentaxim® and hepatitis B” to fully combined vaccine “Hexaxim®” in the Malaysian National Immunization Program

Abstract: Background The decision to implement new vaccines should be supported by public health and economic evaluations. Therefore, this study was primarily designed to evaluate the economic impact of switching from partially combined vaccine (Pentaxim® plus hepatitis B) to fully combined vaccine (Hexaxim®) in the Malaysian National Immunization Program (NIP) and to investigate healthcare professionals (HCPs)’ and parents’/caregivers’ perceptions. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Physicians had many reasons for the unanimous support for the fully liquid hexavalent vaccine since it could probably lead to cost savings for the governmental bodies that provide the cost of the immunization program as shown in an economic evaluation study conducted by Aljunid et al. ( 50 ) where they demonstrated that the fully liquid hexavalent vaccine could reduce the cost per dose and birth cohort if it replaced the non-fully liquid pentavalent and monovalent hepatitis B vaccines in the Malaysian NIP, which would yield significant overall cost savings to the healthcare provider in Malaysia ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physicians had many reasons for the unanimous support for the fully liquid hexavalent vaccine since it could probably lead to cost savings for the governmental bodies that provide the cost of the immunization program as shown in an economic evaluation study conducted by Aljunid et al. ( 50 ) where they demonstrated that the fully liquid hexavalent vaccine could reduce the cost per dose and birth cohort if it replaced the non-fully liquid pentavalent and monovalent hepatitis B vaccines in the Malaysian NIP, which would yield significant overall cost savings to the healthcare provider in Malaysia ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vaccination schedules among separate vaccines in children potentially overlapped, so the combined vaccines would be convenient and achieve favorable cost-effectiveness [ 46 , 47 ]. Recently, a study from Malaysia suggested that the use of a hexavalent DTaP–HBV–IPV–Hib combination vaccine had a lower cost per dose and demonstrated substantial direct and indirect cost savings for healthcare providers and parents [ 48 ]. A study from China in 2019 reported savings of 2.2 billion RMB for families in Guangdong province as a result of the co-administration of multiple vaccines [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…37,38 A study from Malaysia suggested that most parents preferred a combination vaccine to relieve the child's pain and discomfort. 22 The severity of delayed vaccination rises with increasing doses and visits. Significantly, the COVID-19 outbreak aggravated this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have similarly demonstrated that parents wish new vaccinations for children to be available in combination form to avoid the extra pain their infants suffer from getting too many shots or injections 37,38 . A study from Malaysia suggested that most parents preferred a combination vaccine to relieve the child's pain and discomfort 22 . The severity of delayed vaccination rises with increasing doses and visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation